Non-fatal cardiovascular events preceding sudden cardiac death in patients with an acute myocardial infarction complicated by heart failure: insights from the high-risk myocardial infarction database. Issue 2 (28th August 2020) - Hui, Sonya K; Sharma, Abhinav; Docherty, Kieran; McMurray, John J V; Pitt, Bertram; Dickstein, Kenneth; Pfeffer, Marc A; Girerd, Nicolas; Rossignol, Patrick; Ferreira, João Pedro; Zannad, Faiez
Abstract: Aims: Among patients with acute myocardial infarction (AMI) complicated by heart failure [HF; clinical HF or left ventricular (LV) systolic dysfunction], we explored the probability of subsequent non-fatal cardiovascular (CV) events and sudden cardiac death (SCD). Methods and results: The high-risk myocardial infarction (HRMI) database contains 28 771 patients with signs of HF or reduced LV ejection fraction (<40%) after AMI. We evaluated the temporal association between SCD with preceding non-fatal CV event [HF hospitalization, recurrent myocardial infarction (MI), or stroke]. Median follow-up was 1.9 years. Mean age was 65.0 ± 11.5 years and 70% were male. The incidence of CV death was 7.9 per 100 patient-years and for SCD was 3.1 per patient-years (40% of CV deaths). The incidence of SCD preceded by HF hospitalization was greater than SCD without preceding HF hospitalization ( P < 0.05). However, overall, SCD was less likely to be preceded by a non-fatal CV event compared to other causes of death: 9.6% of SCD events were preceded by an MI (vs. 46.6% for non-sudden CV death); 17.0% of SCD events were preceded with an HF hospitalization (vs. 25.4% for non-sudden CV death); and 2.7% of SCD events were preceded by stroke (vs.12.9% for non-sudden CV death). Conclusion: Among patients with AMI complicated by HF, SCD, compared with other causes of death, was less likely to be preceded by a non-fatal CV event. As patients are less likely to have preceding non-fatal CV events to alert the healthcare team of a possible impending SCD event, additional strategies for risk stratification for SCD are needed.